2000
DOI: 10.1002/(sici)1097-0142(20000315)88:6<1378::aid-cncr15>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

The expression of Fhit protein is related inversely to disease progression in patients with breast carcinoma

Abstract: BACKGROUND The FHIT gene, located at human chromosome 3p14.2, frequently is deleted in a number of human tumors, including breast carcinoma. Its protein product (Fhit) is presumed to have tumor suppressor function. Loss of expression of a tumor suppressor gene is an important step in tumor progression from premalignant, to in situ, to invasive carcinoma. METHODS In the current study, Fhit expression was examined in invasive carcinomas and in epithelial lesions representing stages of carcinoma progression in 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 21 publications
(19 reference statements)
5
43
2
Order By: Relevance
“…Furthermore, higher amounts of Fhit protein were measured in wild type controls compared to RET/PTC3 p537/7 specimens (Figure 4a), corresponding with decreased Fhit staining of tumor compared to normal thyroid cells (not shown). These ®ndings are consistent with the expression of Fhit in normal, but not malignant, epithelium (Birrer et al, 1999;Gatalica et al, 2000;Hao et al, 2000;Manning et al, 1999;Mori et al, 2000;Xiao et al, 1997;Yoshino et al, 2000). Similar to RET/PTC3 staining patterns within tumors, no morphological di erences were observed between Fhit positive and negative regions indicating that the appearance of the tumor is not a consequence of Fhit protein loss.…”
Section: Regional Loss Of Fhit Protein Expression In Thyroid Tumorssupporting
confidence: 78%
“…Furthermore, higher amounts of Fhit protein were measured in wild type controls compared to RET/PTC3 p537/7 specimens (Figure 4a), corresponding with decreased Fhit staining of tumor compared to normal thyroid cells (not shown). These ®ndings are consistent with the expression of Fhit in normal, but not malignant, epithelium (Birrer et al, 1999;Gatalica et al, 2000;Hao et al, 2000;Manning et al, 1999;Mori et al, 2000;Xiao et al, 1997;Yoshino et al, 2000). Similar to RET/PTC3 staining patterns within tumors, no morphological di erences were observed between Fhit positive and negative regions indicating that the appearance of the tumor is not a consequence of Fhit protein loss.…”
Section: Regional Loss Of Fhit Protein Expression In Thyroid Tumorssupporting
confidence: 78%
“…29 By contrast, the gap between the percentages of Fhit protein loss versus Fhit aberrant transcripts is wider in breast cancers. Indeed, we and others observed aberrant transcripts expression in 30-35% of breast cancer cases [30][31][32][33][34][35][36] but Fhit protein absence or marked reduction compared to normal epithelium of the same patient in up to 60-70% of cases. 32,34 A wide discrepancy has also been reported in renal carcinomas, where transcript alterations were described in 51% of clear-cells and 10% of papillary sporadic renal carcinoma cells, while absent or Fhit protein reduction occurred in 88% and 26%, respectively.…”
Section: E S B I O S C I E N C E D O N O T D I S T R I B U T Ementioning
confidence: 90%
“…Indeed, we and others observed aberrant transcripts expression in 30-35% of breast cancer cases [30][31][32][33][34][35][36] but Fhit protein absence or marked reduction compared to normal epithelium of the same patient in up to 60-70% of cases. 32,34 A wide discrepancy has also been reported in renal carcinomas, where transcript alterations were described in 51% of clear-cells and 10% of papillary sporadic renal carcinoma cells, while absent or Fhit protein reduction occurred in 88% and 26%, respectively. [37][38][39] Further studies have reported loss of Fhit not due to altered transcript but to promoter hypermethylation of the FHIT gene in breast, gallbladder and NSCL cancers.…”
Section: E S B I O S C I E N C E D O N O T D I S T R I B U T Ementioning
confidence: 90%
“…FHIT and its protein product have been the focus of recent debate with regard to its role in tumorigenesis in bronchial (29), esophageal (30), colorectal (31), breast (32), and cervical (33) cancer. A tumor suppressor role for FHIT was postulated based on the ability of FHIT to eliminate or reduce the tumorigenicity of tumor cells in nude and knockout mice (34,35) and is now widely accepted (6).…”
Section: Discussionmentioning
confidence: 99%